International aspects of merger policy: a survey - Breinlich, Holger; Nocke, Volker; Schutz, Nicolas (Elsevier, 2017)
This paper surveys the literature on merger policy in open economies. We first adopt a reduced-form approach to derive general insights on the scope for conflict between national antitrust authorities and on the gains from international merger policy coordination. Taking trade costs as given, we use standard oligopoly models to derive conditions on market structure, under which underenforcement or overenforcement of national merger policies can arise. We then study the interactions between merger policy and trade policy, and find that trade liberalization often leads to stricter national merger policies. We conclude by discussing empirical evidence on conflict between antitrust authorities.